Effectiveness of knee patellar taping along with exercises in patello femoral pain syndrome - a randomized controlled study - J. ISAAC JASON, (International Journal of Pharma and Bio Sciences, 2016)
The aim of this study is to find out the effectiveness of Patellar taping and Exercises in reducing pain and improving function in subjects with Patello-femoral pain syndrome (PFPS). The study was conducted at Physiotherapy Out-Patient department of Sri Venkateswara Ramanarayana Ruia Government Hospital (SVRRGH), Tirupathi, Andhra pradesh, India. Thirty subjects with patello-femoral pain participated in this study (N=30). They were randomly assigned to one of two treatment groups; 15 subjects for exercises alone group and 15 subjects for patellar taping along with exercises group. Design of the study is experimental and comes under the category of controlled clinical trial. .Functional index questionnaire (FIQ), Visual analog scale (VAS) were used as outcome measures. Taping significantly reduced perceived pain and improves function in subjects with Patello femoral pain. Therefore, taping may be a low cost, non-invasive intervention to relieve symptoms in subjects with Patello-femoral pain.